Socal change in village India - Sachchidananda (New Delhi Concept Publisher, 1988)
This volume is a collection of eighteen research papers published from time to time in different journals by Professor Sachchidananda on changing social realities in Village India. The book is divided into three parts. The first part deals with the impact of the democratic process in independent India on the caste system leading to a change in its nature, the efforts of Mahatma Gandhi for the eradication of untouchability, the emergence of the scheduled caste elite, the rising tide of caste Hindu violence against the Harijans and the changing group relations on account of the policy of protection and discrimination. The second part brings out various facets of rural development such as the strategies adopted by the government, the role of youth in development, problems in reaching development to the rural of youth in development, problems in reaching development to the rural poor, the impact of land reforms on them, the changing character of peasant society in India and the various dimensions of the rural family in west Bihar. The third part details the study of social change in India in historical perspective, the differential impact of television in villages, the role of the voluntary agencies in rural development and the challenges faced by them in the Eighties and the growing ramifications and sociological implications of corruption. Deep sociological insights of the author are reflected in all the papers in this volume.
Keywords: Social change-India